2017
DOI: 10.1038/srep41903
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation map in circulating leukocytes mirrors subcutaneous adipose tissue methylation pattern: a genome-wide analysis from non-obese and obese patients

Abstract: The characterization of the epigenetic changes within the obesity-related adipose tissue will provide new insights to understand this metabolic disorder, but adipose tissue is not easy to sample in population-based studies. We aimed to evaluate the capacity of circulating leukocytes to reflect the adipose tissue-specific DNA methylation status of obesity susceptibility. DNA samples isolated from subcutaneous adipose tissue and circulating leukocytes were hybridized in the Infinium HumanMethylation 450 BeadChip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 57 publications
9
71
2
Order By: Relevance
“…According to Tseng 36 , ZFP36L1 overexpression might repress adipogenesis at least by down-regulating PPARG2 expression. These findings are a proof that blood leukocytes are able to reflect the regulation of same adipose tissue biology-related genes as it was also demonstrated in previous reports 13,[37][38][39] . In the current research, we were unable to detect differences in methylation levels of previously identified obesity related CpG sites, probably because differences in the study design, sample size or the threshold used for selection of candidates.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…According to Tseng 36 , ZFP36L1 overexpression might repress adipogenesis at least by down-regulating PPARG2 expression. These findings are a proof that blood leukocytes are able to reflect the regulation of same adipose tissue biology-related genes as it was also demonstrated in previous reports 13,[37][38][39] . In the current research, we were unable to detect differences in methylation levels of previously identified obesity related CpG sites, probably because differences in the study design, sample size or the threshold used for selection of candidates.…”
Section: Discussionsupporting
confidence: 87%
“…However, the current study adds new information to this issue. In fact, the identified genes were involved in adipose tissue-related pathways that were also observed in previous reports on obesity-related methylation profile 13,38,39 .…”
Section: Discussionsupporting
confidence: 84%
“…Although previous studies support tissue‐specific DNA methylation patterns (Lokk et al., 2014), there is growing evidence in humans suggesting that some methylation marks detected in leukocytes can be reflected in other target tissues, including oral mucosa (San‐Cristobal et al., 2016) and subcutaneous adipose tissue (Crujeiras et al., 2017). Also, homologies between genomic signatures (including DNA methylation patterns) from blood and brain were reported in a rodent model of concussive injury (Meng et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Modifications in the gene expression profile observed in hASCs according to the methylation pattern were also explored in PBMCs, as they represent a more accessible source for sampling. Also, epigenetic modifications to hASCs might be reflected in peripheral blood, as already demonstrated in other inflammatory diseases such as obesity [45]. Indeed, changes to the PBMC methylome in CD have previously been described, revealing that differentially methylated genes implicated in immune response are the most frequently affected [19,46].…”
Section: Verification Of Candidate Genes In Circulating Pbmcs In Patimentioning
confidence: 69%